PERLINDUNGAN HAM MELALUI PENGUJIAN UNDANG-UNDANG OLEH MAHKAMAH KONSTITUSI - Titon Slamet Kurnia (Yuridika, 2015)
The MKRI is a new governmental body which was established under the Third Amendment of the UUD NRI 1945. This article examines its proper function which underlies its jurisdiction to review the constitutionality of legislation. According to the issue, this article argues that the MKRI should be treated as a human rights court whenever it undertakes its jurisdiction to review the constitutionality of legislation. The function of the MKRI as a human rights court justifies its existence and also prescribes principles for its operation. It means that in reviewing the constitutionality of legislation the MKRI should enhance the protection of human rights through its judicial policy and constitutional interpretation.Keywords: MKRI, function, human rights court